Resistance Training Data Analysis on Blood and Personal Profiles for Customized Healthcare - Wi-Young SO; Taikyeong Ted. J EONG (Tehran University of Medical Sciences, 2018)
Resistance Training Data Analysis on Blood and Personal Pro-files for Customized Healthcare